(untitled) (Baghdad Science Journal, 2025)
Molecular interactions between 2-isopropenylnaphthalene-methacrylic acid (IPNMA) block copolymer( as a model for water- soluble polymer) and methanol at several temperatures were studied using fluorescence techniques , Fluorescence spectrum for (IPNMA) exhibits two emission bands at around 342 nm and 387 nm corresponding to the monomer and the excimer bands , respectively .The fluorescence spectra of dilute solution of (IPNMA) in methanol were recorded in temperature range of 8- 45?C . Plot of the excimer to monomer intensity ratio Ie/Im versus temperature was obtained, which shows double lines with positive slopes crossing at 25?C , the increasing of slope value above this temperature is small which indicates that there is stronger solvation of methanol molecules to polymer coil at temperature below 25? C arising from hydrogen bond formation between the polymer and the solvent .